REALITAS SOSIAL DALAM NASKAH DRAMA RT NOL RW NOL KARYA IWAN SIMATUPANG (KAJIAN REALISME SOSIALIS GEORG LUKACS) - Sam, Nurfatmawati; Hajrah, Hajrah; Faisal, Faisal (Fakultas Bahasa dan Sastra Indoensia, 2026)
This study aims to describe the forms of social reality in Iwan Simatupang’s drama RT Nol RW Nol based on Georg Lukacs’s theory of Socialist Realism. Using a qualitative descriptive method with a sociology of literature approach, the research focuses on four main aspects: objective reality, dialectical movement, artistic reflection, and emancipatory critical expression. The findings show that the drama reflects social inequality, poverty, and marginalization, while also portraying human awareness and resistance against oppression. Iwan Simatupang’s work illustrates the dialectical relation between individuals and society, emphasizing the human struggle for dignity and freedom.This study aims to describe the forms of social reality in Iwan Simatupang’s drama RT Nol RW Nol based on Georg Lukacs’s theory of Socialist Realism. Using a qualitative descriptive method with a sociology of literature approach, the research focuses on four main aspects: objective reality, dialectical movement, artistic reflection, and emancipatory critical expression. The findings show that the drama reflects social inequality, poverty, and marginalization, while also portraying human awareness and resistance against oppression. Iwan Simatupang’s work illustrates the dialectical relation between individuals and society, emphasizing the human struggle for dignity and freedom.